ClariVein™ – One year results of mechano-chemical ablation for varicose veins in a multi-ethnic Asian population from Singapore. (December 2018) - Khor, Shao N; Lei, Jiang; Kam, Jia W; Kum, Steven; Tan, Yih K; Tang, Tjun Y
Objectives: This study assessed the effectiveness and patient experience of ClariVein for varicose veins and chronic venous insufficiency (CVI) in a multi-ethnic Asian population from Singapore. Methods: A total of 121 patients underwent mechano-chemical ablation. Patients were reviewed at an interval of one week, and at 3, 6 and 12 months post procedure and underwent Duplex ultrasound with patient satisfaction assessment. Results: At three months of follow-up, the great saphenous vein and short saphenous vein occlusion rates were 90.8% and 96.0%, respectively. At six months of follow–up, the GSV and short saphenous vein occlusion rates were 86.9% and 90.9%, respectively. At one year, great saphenous vein and short saphenous vein occlusion rates were 84.8% and 94.3%, respectively. Conclusions: Early results are similar to what is described so far in the mechano-chemical ablation literature but recurrences are more than expected at one year. This is disappointing but is tempered by the fact that the majority of patients were asymptomatic and required no reintervention.